Pathophysiology of blood-brain barrier in brain tumor. Novel therapeutic advances using nanomedicine - Sharma H.S.; Muresanu D.F.; Castellani R.J.; Nozari A.; Lafuente J.V.; Tian Z.R.; Sahib S.; Bryukhovetskiy I.; Bryukhovetskiy A.; Buzoianu A.D.; Patnaik R.; Wiklund L.; Sharma A. (My University, 2025)
Glioblastoma Multiforme (GBM) is one the most common intracranial tumors discovered by Burns (1800) and Abernethy (1804) based on gross morphology of the autopsied material and referred to as “medullary sarcoma” and later “fungus medullare” (Abernethy, 1804; Burns, 1800). Virchow in 1863 was the first German pathologist using histomorphological techniques discovered that GBM is a tumor of glial origin. Virchow (1863/65) also then used the term Glioma for the first time and classified as low-grade glioma and high-grade glioma very similar to that of today according to World health organization (WHO) classification (Jellinger, 1978; Virchow, 1863/65). After almost > 50 years of this discovery, Baily and Cushing (1926) based on modern neuropathological tools provide the classification of gliomas that is still valid today (Baily & Cushing, 1926). Although, our knowledge about development of gliomas has advanced through development of modern cellular and molecular biological tools (Gately, McLachlan, Dowling, & Philip, 2017; Omuro & DeAngelis, 2013), therapeutic advancement of GBM still requires lot of efforts for the benefit of patients. This review summarizes new developments on pathophysiological aspects of GBM and novel therapeutic strategies to enhance quality of life of patients. These novel therapeutic approaches rely on enhanced penetration of drug therapy into the tumor tissues by use of nanomedicine for both the diagnostic and therapeutic purposes, referred to as “theranostic nanomedicine” (Alphandéry, 2020; Zhao, van Straten, Broekman, Préat, & Schiffelers, 2020). Although, the blood-brain barrier (BBB) is fenestrated around the periphery of the tumor tissues, the BBB is still tight within the deeper tissues of the tumor. Thus, drug delivery is a challenge for gliomas and requires new therapeutic advances (Zhao et al., 2020). Associated edema development around tumor tissues is another factor hindering therapeutic effects (Liu, Mei, & Lin, 2013). These factors are discussed in details using novel therapeutic advances in gliomas. © 2020 Elsevier Inc.